2015
DOI: 10.1074/jbc.m115.646638
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) Polymerase 1 Modulates Interaction of the Nucleotide Excision Repair Factor XPC-RAD23B with DNA via Poly(ADP-ribosyl)ation

Abstract: Background: Poly(ADP-ribosyl)ation of DNA repair proteins is essential for the regulation of DNA repair processes. Results: Both subunits of the nucleotide excision repair factor XPC-RAD23B are poly(ADP-ribosyl)ated by PARP1. Conclusion: PARP1 influences the interaction of XPC-RAD23B with DNA via PAR synthesis. Significance: This study provides direct evidence for XPC-RAD23B belonging to the targets of poly(ADP-ribosyl)ation catalyzed by PARP1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 37 publications
(43 reference statements)
1
17
1
Order By: Relevance
“…The synthesis of radioactive NAD + was carried out from α−[ 32 P]-ATP according to [ 81 ] with modification described in [ 82 ]. The reaction mixtures containing 1 mM ATP, 10 MBq of α−[ 32 P]-ATP, 20 mM MgCl 2 , 2 mM β-nicotinamide mononucleotide, and 5 mg/ml nicotinamide nucleotide adenylyltransferase in 25 mM Tris-HCl, pH7.5 were incubated at 37ºC for 60 min, then stopped by heating up to 90ºC for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of radioactive NAD + was carried out from α−[ 32 P]-ATP according to [ 81 ] with modification described in [ 82 ]. The reaction mixtures containing 1 mM ATP, 10 MBq of α−[ 32 P]-ATP, 20 mM MgCl 2 , 2 mM β-nicotinamide mononucleotide, and 5 mg/ml nicotinamide nucleotide adenylyltransferase in 25 mM Tris-HCl, pH7.5 were incubated at 37ºC for 60 min, then stopped by heating up to 90ºC for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…DDB2 PARylation leads to the protein’s stabilization and further recruitment [92]. Furthermore, Maltseva et al demonstrated that XPC-RAD23B, an essential complex of the NER pathway, is regulated by PARP-1 [93]. Induction of the NER pathway by platinum-based agents and simultaneous inhibition of PARP-1 could potentially suppress DNA repair.…”
Section: Combination Therapy Using Platinum-based Agents and Ddr-targmentioning
confidence: 99%
“…64 It was further demonstrated that both XPC and RAD23B are parylated by PARP1 in response to UV irradiation. 65 Whether parylation of these factors is linked to ubiquitylation events as observed for DDB2 is currently unclear but an attractive speculation. Further, XPA shows high affinity for long PAR chains 66 suggesting that parylation might also play a role during damage verification.…”
Section: Regulation Of Poly-ubiquitylation By Parylation and Deubiquimentioning
confidence: 99%